PENGARUH BRAND EXTENSION SABUN MANDI LIFEBUOY KE SAMPO LIFEBUOY TERHADAP KEPUTUSAN MEMBELI KONSUMEN DI FAKULTAS PERTANIAN UNIVERSITAS SUMATERA UTARA - manajemen FEUSU (Universitas Sumatera Utara, 2013)
ABSTRACT This research aims to determine and analyze of effects of brand extension lifebuoy soap to lifebuoy shampoo for the decision of cumsumers buying at Faculty of Economic University of North Sumatera. The Sampling technique use a accidental sampling method. The target of population are Faculty at Agriculture University of North Sumatera who had purchased, use students lifebuoy soap and lifebuoy shampoo . The primary data ware collected by distributing questionnaires to students Agriculture Faculty unversity north sumatera student, Medan, use lifebuoy soap and lifebuoy shampoo and 100 students ware used as the samples. This research use data by questionnaire and documentation. Measured data use Likert scale. The hypothesis testing use simple regression linear analysis. The results of this research in that brand extension lifebouy soap lifebuoy shampoo influence positively and significant effectly the decision of consumers buying at Faculty of Agriculture University of North Sumatera. Rated R sequare = 37,7% which mean of the relation of variabel is tight enough. Keyword: Brand Extension and Buying Decision